KALIMAT INVERSI DALAM BAHASA INDONESIA - Bambang Eko Cahyono (Indonesian Language Education and Literature, 2016)
In the Indonesian language there is one type of sentence, that sentence inversion. Inversion sentence is sentence structure subject precedes predicate function (P-S). Based on the results of data analysis, there are several types of sequence patterns syntactic function contained in the phrase inversion Indonesian namely (1) PS, (2) POS, (3) P-Pel-S, (4) PO-Pel-S, (5) PS with Specification, (6) POS with Description, (7) P-Pel-S with the description, and (8) PO-Pel-S with a description. Also there are different types of sentences in the sentences Indonesian inversion which consists of: (1) sentence declarative inversion which is divided into two types of patterns that can be converted into the S-P and type that can not be converted into P-S; (2) The inversion of interrogative sentences are divided into two inversions interrogative sentences that require yes or no answers and inversion interrogative sentences that require answers explanatory; (3) sentence inversion imperative which is divided into two inversions imperative sentences with active diathesis and passive sentences with inversion imperative diathesis; and (4) the sentence exlasamative.Â